External intervention to strengthen democracy in Africa - GIGA German Institute of Global and Area Studies - Leibniz-Institut für Globale und Regionale Studien, Institut für Afrika-Kunde (2016)
Abstract: Although more competitive forms of authoritarianism and electoral democracy are today prevalent in most African countries, democratisation has slowed and in some places reversed. This coincides with an ever-growing rift between African citizens who are demanding further democratic rights and rulers who want to preserve their prerogatives. Western actors need to support those who hold the greatest democratic aspirations more fervently: African citizens themselves